The Online Course as Initial Stage of a Course in Higher Education: Implementation and Evaluation of the Pre-MOOC Concept in a Technical Degree Course - Braun, Clarissa; Ebner, Martin; Fickert, Lothar H.; Schön, Sandra (International Journal of Emerging Technologies in Learning (iJET), 2021)
In university teaching, a MOOC is often regarded as an isolated online course and thus underestimated in its didactic application possibilities within traditional teaching and learning environments. In this study, the "Pre-MOOC" design is presented as an example, in which the didactic em-bedding of an online course is the first phase of a lecture in higher educa-tion. After a brief overview of the current state of research on Pre-MOOCs, the article describes the instructional design process of the lecture in which we used the instructional design model ADDIE. Furthermore, the study de-scribes the implementation and evaluation in a master program of electrical engineering. We will analyze the results of the evaluation with regard to the concept of a Pre-MOOC. Based on feedback from students and teachers, rec-ommendations for designing a course with the Pre-MOOC design will be provided.